Design Translation Application from Indonesian to the Nyow Dialect (Pepadun) Based on Android - Sunardi; Yunan Henryanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2022)
Language is a sign to communicate. In the world, there are many languages ​​that characterize the country, for example, the State of Indonesia has various regional languages, one of which is the Nyow Dialect (Pepadun) which is dominantly used by residents in the coastal Lampung area to communicate. The purpose of this research is to design and build an Android-based digital dictionary application that can be used to make it easier to find translated vocabulary either in Indonesian or in the Nyow Dialect (Pepadun) so that it can be used in general so as to provide convenience for the wearer. The method used in this thesis is the prototyping method. Based on the test results on the Android-based Indonesian-Now Dialect (Pepadun) application, it can be seen and can conclude several things as follows; The search system designed is able to display words in the database more quickly and equivalently, the search process is carried out by an implicit system where the words to be searched will be processed based on an array that matches the user input string, and system design with Xamarin in the Visual Studio 2017 application package. as an android programming language toll in making applications, it is right because of the ease in the application development process.